Improved Medication Management With Introduction of a Perioperative and Prescribing Pharmacist Service. (June 2020) - Nguyen, Anny D.; Lam, Alice; Banakh, Iouri; Lam, Skip; Crofts, Tyron
Background: The medication lists in pre-admission clinic (PAC) questionnaires completed by patients prior to surgery are often inaccurate, potentially leading to medication errors during hospitalization. Studies have shown pharmacists are more accurate when obtaining a medication history and transcribing prescription orders, thereby reducing errors. Objective: To evaluate the impact of a PeRiopErative and Prescribing (PREP) pharmacist on postoperative medication management. Methods: A randomized prospective interventional study enrolled elective surgery patients at high risk for medication misadventure to receive PREP pharmacy service or usual care (control group). A best possible medication history (BPMH) was obtained by the PREP pharmacist and was available to surgical staff on admission. The PREP pharmacist also prepared discharge prescriptions for their patients. The primary outcomes for the study were accuracy of BPMH and discharge prescriptions compared to usual care. The study was powered to 80% with 2-tailed significance α of .05. Results: The medication history in the PREP pharmacist group had fewer errors than the control group: 9% (5/53) versus 96% (49/51; P < .001). Discharge prescriptions prepared by the PREP pharmacist had fewer errors than control group: 25% versus 78% ( P < .001). Significantly, more PREP pharmacist patients received a discharge summary with a complete medication list: 75% versus 33% ( P = .001). Inpatient prescribing was more accurate in the PREP pharmacist patients: 0.64 versus 1.31 errors per patient ( P = .047). Conclusion: Inclusion of the PREP pharmacist role in the elective surgery multidisciplinary team improved the accuracy of medication histories, inpatient prescribing, and discharge prescriptions for patients at high risk of medication misadventure.